Migrant nation : Australian culture, society and identity - Arthur, Paul Longley (Anthem studies in Australian literature and culture., 2018)
'Migrant Nation: Australian Culture, Society and Identity' casts new light on Australian identity through historical accounts of the many and varied experiences of migration.